(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
Nowadays, most mining and quarrying industries utilize a diamond wire saw machine for bench cutting operations. This method uses a metal wire or cable assembled by diamond beads to cut the hard stone into large blocks. Many parameters classified into controllable and uncontrollable parameters affect the performance of the diamond wire saw cutting method. The uncontrollable parameters are related to rock engineering properties, and controllable parameters are related to operational aspects and machine performance. The diamond wire sawing process’s production rate is one of the most critical parameters influencing the design optimization and quarrying cost estimation. The cutting rate and wear rate of diamond beads are the most important factors to evaluate quarries’ production performance. This study aims to determine the effects of different controllable and uncontrollable parameters on different quarries’ production rates. Rock engineering properties like strength, hardness, and abrasivity, and operational aspects, such as cutting angle and drive wheel diameters, are considered as the main factors affecting the production performance of the diamond wire saw method. To discover the influence of these parameters, a detailed investigation in ten quarry operations was carried out. The relation between cutting rate and diamond bead wear with different parameters is estimated. It was observed that different controllable and uncontrollable parameters could increase or decrease the cutting rate and diamond bead wearing. Furthermore, using simple and multiple regression analysis, performance prediction of the cutting rate and wearing of diamond beads was developed, and the best equations were proposed.